The Effect of Amount of Mixed Garlic Extract with Spinach and Sugar on The Quality of Instant Germinated Soya Drink - Fitra Yanti Situmorang; Ismed Suhaidi; Setyohadi Setyohadi (Jurnal Rekayasa Pangan dan Pertanian, 2015)
This study was aimed to determine the effect of mixed of  garlic extract  with spinach and amount of sugar on the quality of instant germinated soya drink. Complete Randomised Design (CRD) with 2 factors were used: the ratio of garlic and spinach extract (0.5%: 4.5%, 1.0%: 4.0%, 1.5%: 3.5 %, 2.0%: 3.0%) and the amount of sugar (10%, 20%, 30%, 40%). Parameters measured were fat content, water content, protein content, solubility, taste, aroma and color. The results showed that the ratio of garlic extract mix and spinach had a highly significant effect on fat content, water content, protein content, solubility, taste, aroma and color. The effect of  the amount of sugar was differed significantly on fat content, water content, protein content, solubility, taste, aroma and color. Interaction of both factors were significantly  affected the solubility and not significantly effected the fat content, water content, protein content, taste, aroma and color. To produce quality of instant germinated soya drink suggested to used the ratio of garlic and spinach extract 0,5:4,5% and the amount of sugar 10%.